2017
DOI: 10.1039/c7tc03669h
|View full text |Cite
|
Sign up to set email alerts
|

All inkjet-printed graphene-based conductive patterns for wearable e-textile applications

Abstract: We report inkjet printing of an organic nanoparticle-based surface pre-treatment onto textiles to enable all inkjet-printed graphene e-textiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
199
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(201 citation statements)
references
References 59 publications
2
199
0
Order By: Relevance
“…After the vaporization of the solvent, the GO coating could be treated with reducing agents, resulting in a conductive reduced GO (rGO) coating surrounding the fiber . Karim et al found that the adhesion and continuity of rGO coatings could be enhanced by a predeposition of polymer interlayer . On the other hand, inks based on metal precursors endows a metallic coating with higher conductivity than rGO ( Figure a,b), while the tendency for oxidation and high cost might restrain their use.…”
Section: Fabrication Processes Of Components For Stimesmentioning
confidence: 99%
See 1 more Smart Citation
“…After the vaporization of the solvent, the GO coating could be treated with reducing agents, resulting in a conductive reduced GO (rGO) coating surrounding the fiber . Karim et al found that the adhesion and continuity of rGO coatings could be enhanced by a predeposition of polymer interlayer . On the other hand, inks based on metal precursors endows a metallic coating with higher conductivity than rGO ( Figure a,b), while the tendency for oxidation and high cost might restrain their use.…”
Section: Fabrication Processes Of Components For Stimesmentioning
confidence: 99%
“…Tracking the electrocardiogram (ECG) of human beings could provide not only an alert of acute cardiovascular malfunctions, but much information about physical conditions from the ECG waveforms. In e‐textile based ECG monitoring system, the working and reference electrodes fabricated on textiles could be separately contacted to the two upper limbs of the wearer (Figure e), which could provide ECG recording with high signal‐to‐noise ratio and long term stability (Figure f) . On the other hand, many ultrasensitive e‐textile based mechanical sensors enable the recording of wrist pulses, by which the indicators of age, gender as well as some diseases, such as hypertension, could be reflected.…”
Section: Wearable Applications Of Stimesmentioning
confidence: 99%
“…Finally, the circuit traces can be released from the tattoo paper and transferred to 3D surfaces or human skin (Figure f). All inkjet‐printed graphene‐based wearable e‐textiles were also realized . Hydroxyl‐functionalized cross‐linked styrene/divinylbenzene NPs were first inkjet printed on a porous textile substrate to act as a receptor layer for water‐based RGO inks.…”
Section: Applications: Flexible and Stretchable Devicesmentioning
confidence: 99%
“…In recent years, electronic textiles (e-textiles) have attracted significant research attention with respect to the development of new biological information monitoring systems [1][2][3][4][5][6], human interface systems [7,8], and fashions [9,10], among other schemes [11][12][13][14][15][16][17][18]. At present, only conductive tracks and pads and several types of sensors can be formed on a textile by weaving, knitting, and stitching of conductive yarns on the textile [9,[19][20][21], or by printing of conductive inks on the textiles [3,22,23].…”
Section: Introductionmentioning
confidence: 99%